Irrigation Of Gardens From Modern Innovative Technologies Which Are Very Low Waste In Dry Land With Digital Automatic Methods - F.Q.Shakarov; M.K.Haqqulov; S.Q.Axadov; S.Y.Mahmudov (Zien Journals, 2022)
This article provides information and examples of methods of garden irrigation and mineral nutrition using modern innovative technologies that are very wasteful in dry lands using digital automated methods.
Keywords: irrigation; mineral nutrition; garden irrigation; arable land